Non-volatile logic device based on domain-wall motion in a biaxial magnetic tunnel junction. (26th January 2021) - Li, Shuping; Cai, Jialin; Lv, Wenxing; Zhang, Like; Liang, Shiheng; Zeng, Zhongming
Abstract: We report on the non-volatile logic device based on domain-wall (DW) motion in a biaxial magnetic tunnel junction (MTJ) where the shape-induced magnetic anisotropy of the free layer is orthogonal to the easy axis of the reference layer. Different switching behaviors have been observed while applying either a magnetic field or current to reverse the MTJ. By denoting the magnetic field and current as two independent logical input, multiple logical operations such as "OR", "AND" and "NOT" have been performed in a device with different initial states. These results show that DW-based devices have the potential for future computing hardware.